The Cycle of Child Protection Services Involvement: A Cohort Study of Adolescent Mothers - Wall-Wieler, Elizabeth; Brownell, Marni; Singal, Deepa; Nickel, Nathan; Roos, Leslie (International Journal of Population Data Science, 2018)
Introduction Adolescent girls in care of child protection services are more likely to become pregnant than adolescent girls not in care, and mothers who were in care are more likely to have their children placed in care. Objectives and Approach Linkable administrative data were used to determine whether adolescent mothers in care are at greater risk of having their child placed in care before age two. A population-based cohort of adolescent mothers whose first child was born in Manitoba, Canada between April 1, 1998, and March 31, 2013 (n = 5,942) was used. Adjusted odds ratios (AOR) of having that first child taken into care before their second birthday were compared between mothers who were in care (n = 576) and mothers who were not in care (n = 5, 366) at the birth of their child using logistic regression models. Results Adolescent mothers who were in care had greater odds of having their child taken into care before the child’s second birthday (AOR = 7.53; 95% CI = 6.19-9.14). Specifically, their children had higher odds of being taken into care in their first week of life (AOR = 11.64; 95% CI = 8.83-15.34), between one week and their first birthday (AOR = 3.63; 95% CI = 2.79-4.71)., and between their first and second birthday (AOR = 2.21; 95% CI = 1.53-3.19). Conclusion/Implications Findings support an intergenerational cycle of involvement with child protection services. More and better services are required for adolescent mothers who give birth while in care of child protection services.